UPAYA GURU DALAM MENANAMKAN KEDISIPLINAN DAN KEMANDIRIAN SISWA MA BUSTANUL ‘ULUM JAYASAKTI - Sari, Nurdiana; Huda Yana, Hawwin; Yuwanita (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
This study aims to reveal and analyze the teacher's efforts in instilling student discipline and independence at MA Bustanul 'Ulum Jayasakti. This research is motivated by the problem of low levels of student discipline and independence which is a challenge for teachers in shaping student character in a pesantren environment. A qualitative approach with the type of field research was chosen because it allows in-depth exploration of social phenomena that cannot be quantified, including processes, events, and authenticity of data. Data were collected through observation, interviews, and documentation, then analyzed descriptively to understand the patterns and strategies applied by teachers in shaping students' disciplinary and independent characters. The findings show that teachers play a central role through the implementation of clear rules, rewards and sanctions, individual guidance, and active communication with parents. Restorative approaches and character education are also applied to help students understand and correct mistakes. This research contributes to understanding character education strategies in pesantren-based educational institutions and provides recommendations for the development of more comprehensive learning models. The findings are relevant to support improving the quality of character education in the modern era.